2018
DOI: 10.5565/rev/doblele.40
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulario emocional en la producción oral en español como lengua de migración

Abstract: Vocabulario emocional en la producción oral en español como lengua de migración 1Emotional Vocabulary in Oral Production of Migrant Learners of Spanish IRINI MAVROU / FERNANDO BUSTOS-LÓPEZ UNIVERSIDAD ANTONIO DE NEBRIJA emavrou@nebrija.es / fbustos@nebrija.es Resumen: El presente estudio analizó el vocabulario emocional en la producción oral de un grupo de adultos inmigrantes aprendientes de español. Los principales resultados fueron los siguientes: (a) casi un tercio del discurso de estos informantes estuvo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…Furthermore, although proxies are convenient, future studies should try to employ standardized tests of L1 literacy, as well as a wider range of L2 writing tasks and more varied L2 writing measures (both product- and process-based). As emotions are always embedded in writing, future research should also address the extent to which linguistic distance is a proxy for emotional detachment by examining the emotional dimensions of the texts produced by immigrants (see e.g., Mavrou & Bustos-López, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although proxies are convenient, future studies should try to employ standardized tests of L1 literacy, as well as a wider range of L2 writing tasks and more varied L2 writing measures (both product- and process-based). As emotions are always embedded in writing, future research should also address the extent to which linguistic distance is a proxy for emotional detachment by examining the emotional dimensions of the texts produced by immigrants (see e.g., Mavrou & Bustos-López, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of recent studies have examined the affective properties (valence and arousal) of the emotional vocabulary used by L2 speakers (e.g. Jiménez Catalán & Dewaele, 2017; Kyriakou & Mavrou, 2022; Mavrou, 2021; Mavrou & Bustos-López, 2018 ; Pavlenko & Driagina, 2007; Pérez-García & Sánchez, 2020; Vidal Noguera et al, 2022). For example, Pavlenko and Driagina (2007) analysed and compared the size and richness of the emotional vocabulary in oral narratives produced by monolingual Russian speakers, monolingual American speakers, and Americans who were highly proficient in Russian.…”
Section: Emotional Expressionmentioning
confidence: 99%
“…Their findings showed that American learners of Russian produced a significantly lower proportion of emotion word. Mavrou and Bustos-López (2018) focused on the valence of the emotional vocabulary used by migrant learners of Spanish in the speaking section of a certification exam. Around one-third of the discourse of these migrants included emotional words, particularly positively valenced words.…”
Section: Emotional Expressionmentioning
confidence: 99%
“…La lengua materna se aprende en contextos cercanos y, por lo tanto, emocionalmente significativos, al contrario que las lenguas extranjeras, las cuales normalmente se aprenden en contextos académicos, donde la carga emocional es mucho menor (Ivaz, Costa y Duñabeitia, 2016). Por lo tanto, es frecuente que en la lengua materna se cuente con un mayor vocabulario emocional que en las lenguas extranjeras (Mavrou y Bustos-López, 2018). En definitiva, la educación emocional es muy importante para tener bienestar y saber actuar ante las diferentes situaciones que se encuentran el día a día.…”
Section: Conciencia Y Vocabulario Emocionalunclassified